STEAM-based Learning to Enhance Early Childhood Creativity - Atikah, Cucu; Biru, Lulu Tunjung (International Journal of STEM Education for Sustainability, 2024)
This study aimed to determine the application of STEAM Education-based learning to improve early childhood creativity abilities. A literature review conducted to gathering and evaluating library data and connecting it to research to find solutions to issues. The study's conclusion is that early childhood creativity can be enhanced by the STEAM approach. High creativity is characterized by flexible thinking, innovative thinking, detailed/elaborative thinking, and fluid thinking.